How Land Finance Drives Urban Expansion under Fiscal Pressure: Evidence from Chinese Cities - De Tong; Jun Chu; Qing Han; Xuan Liu (Land, 2022)
Urban expansion is commonly attributed to market-oriented forces, while public finance factors connected to government forces, especially land finance, in China’s institutional environment, can provide a more interesting explanation. Using a fixed-effect threshold model, the relationships of land finance and differing local fiscal pressures to urban expansion in China were explored mathematically and empirically. It was found that land finance positively and significantly influences urban expansion. It was also found that the impact of land finance on urban spatial size varies with fiscal pressure. Results suggested that capital flows in the process of urban expansion should be carefully regulated by local governments.